Alginate oligosaccharide alleviates senile osteoporosis via the RANKL–RANK pathway in D‐galactose‐induced C57BL/6J mice. (18th November 2021) - Wang, Shan; Feng, Wenjing; Liu, Jianya; Wang, Xufu; Zhong, Lina; Lv, Chengxiu; Feng, Meiping; An, Nina; Mao, Yongjun
Abstract: Osteoporosis is a systemic skeletal disorder characterized by reduced bone mineral density (BMD) and bone quality and increased bone porosity, which increase the risk of bone fracture. Inflammation, one of the important mechanisms related to aging, is associated with osteoporosis. Treatment with anti‐inflammatory agents is effective for alleviating senile osteoporosis. Alginate oligosaccharide (AOS) can prevent and treat diseases related to inflammation, oxidative stress, and immunity. This study evaluates the effect of AOS on osteoporosis and investigates the underlying mechanism. Osteoporosis model was induced by D‐galactose (D‐gal) (200 mg kg −1  day −1 ) for eight weeks. Three groups were administered via AOS (50, 100, and 150 mg kg −1  day −1 ) for four weeks, while a control group received sterile water (5 ml kg −1  day −1 ) for 8 weeks. The results showed that AOS improved bone density and bone microstructure in D‐gal‐induced osteoporosis mice. AOS inhibited osteoclast proliferation, probably through the suppression of receptor activator of nuclear factor‐kappa B ligand (RANKL)‐associated nuclear factor kappa B (NF‐κB) and c‐Fos signaling pathway. AOS also increased osteoprotegerin (OPG) expression and competitively inhibited the binding between RANK and RANKL in senile osteoporosis. Further, AOS decreased the secretion of serum osteocalcin and reduced bone conversion. Together, these results demonstrate the anti‐osteoporosis activity of AOS in mice with osteoporosis. Abstract : Osteoporosis is a systemic skeletal disorder characterized by reduced bone mineral density (BMD) and bone quality and increased bone porosity, which increase the risk of bone fracture. AOS improved bone density and bone microstructure in D‐gal‐induced osteoporosis mice.